Pusaka Sakinah sebagai Upaya Penurunan Angka Perceraian oleh KUA Kiaracondong dan KUA Cipeudeuy di Jawa Barat - Wahidah R Bulan; Kustini Kosasih (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
The high divorce rate encourages the Ministry of Religion to make various efforts to maintain family resilience. The Service Center Program of Sakinah Family or Program Pusat Layanan Keluarga Sakinah (Pusaka Sakinah) is one of the Ministry of Religion’s effort through the transformation of KUA’s role into a more significant in protecting Indonesian families from divorce. This article aims to get an overview of KUA's activities in implementing the Pusaka Sakinah program including the forms of innovation and initiative in pursuing program sustainability. The research method uses qualitative methode through case study type with the locus at KUA Kiaracondong representing program implementation in urban areas, and at KUA Cipeundeuy representing program implementation in rural areas. This study uses the theory of AGIL Structural Functionalism (Adaptation, Goal-attainment, Integration, Latency). This research results several findings: first, although the increasing role of KUA in facilitating the people to actualize sakinah family can be realized through the implementation of the Pusaka Sakinah program, efforts to maintain program sustainability are not an easy way due to KUA's high dependency on the institution in financing the program. Second, initiative and innovation are relatively limited because the concept of the Pusaka Sakinah program has not been understood and there has even been a misinterpretation on transforming KUA, causing disorientation, reduction, and even rejection of programs that are seen as burdensome to KUA. Third, the synergy of implementation program with similar programs carried out by other ministries and local governments is still low. In this regard, the Ministry of Religion needs to make efforts to increase the intended synergy which will also have a positive impact on the availability of resources in program implementation.